Cytokeratin-positive interstitial reticulum cell (CIRC) tumor in the lymph node: a case report of the transformation from the epithelioid cell type to the spindle cell type - Sachiko Kaji; Nobuyuki Hiruta; Daisuke Sasai; Makoto Nagashima; Rintaro Ohe; Mitsunori Yamakawa (BMC, 2020)
Abstract Background Cytokeratin-positive interstitial reticulum cells (CIRCs), which are a subgroup of fibroblastic reticular cells (FRCs), are known to be present in the lymph nodes. There have been only a few cases of tumors derived from CIRCs. Case presentation We have reported a new case involving a CIRC tumor in a 75-year-old man and reviewed the literature. The resected mediastinal lymph nodes showed epithelial-like proliferation of large atypical round and polygonal epithelioid cells. The tumor cells expressed CK8, CK18, CAM5.2, AE1/AE3, epithelial membrane antigen, vimentin, fascin, and some FRC markers, which is consistent with the diagnosis of a CIRC tumor. Following chemotherapy, the CIRC tumor was observed to have responded very well and became difficult to confirm on imaging, but a small cell lung carcinoma developed 12 months later. Chemoradiotherapy was performed, but the patient passed away 29 months after the initial diagnosis. The autopsy revealed the recurrence of the CIRC tumor, residual small cell lung carcinoma, and a very small latent carcinoma of the prostate. The relapsed CIRC tumor cells had a spindle shape; they were highly pleomorphic and had invaded the superior vena cava. Conclusion We first reported autopsy findings of CIRC tumors and demonstrated the transformation of the tumor from the epithelioid cell type to the spindle cell type.